A study on palmistry color reflectance related to personality of subject: article / Abdul Hadi Azman - Azman, Abdul Hadi (2007)
-Palmistry technique is traditionally known as an ancient art of reading the palm and it can be found in many parts of the world. Since blood circulation in the palm contains valuable information about the health condition of a person, this technique is also acts as one of the aid tools for diagnosing purposes. This paper presents a contribution in the field of color image processing of palmistry with the help of advanced RGB color image processing techniques in order to study the personality index of a subject. In this work, samples of palm images are digitally captured under standard and control environment. Other characteristic parameters representing the subject’s personality are also taken. Statistical tools are applied to the quantified color component indices from the processed image for significant findings that can relate color of palm with respect to the subject’s character.